Gender and the distribution of wealth in developing countries - Carmen Diana Deere; Cheryl R. Doss (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Only recently has it been recognized that women may not share in the wealth of men, even within the same household or family. Moreover, there is growing evidence that the gender distribution of wealth matters. This paper first reviews the available evidence for developing countries on the gender asset gap and finds that it is significant. It then considers the constraints on women's asset ownership with particular attention to the role of legal marital and inheritance regimes. The paper then turns to a more detailed examination of women's land ownership in Latin America and Africa. The final section considers the impact of women's land ownership on household income and welfare. – women ; assets ; gender inequality ; marital regimes ; inheritance ; land ; Latin America ; Africa ; law
Keywords: J16; D31; P48; O13; 330; Vermögen; Geschlecht; Grundbesitz; Entwicklungsländer; Lateinamerika